Penyelesaian tuntutan dan sistem timbangtara dalam industri pembinaan di Indonesia - Saleh, Nursyam (2007)
Construction is one of important industries that contribute to the economic growth of Indonesia. However as in any other countries dispute and claim in contruction projects are quite common in this country. Therefore this situation of claim and dispute between the owner and contractor need to be managed professionally and effectively. This study has been conducted with the focus toward addressing the issues related to the claim and dispute in Indonesia Contruction Industry. Among the aspects that had been studied included the main causes of the claim, their implication and various approaches in resolving the claim. Also being studied was the effectiveness of the role of Badan Arbitrase Nasional Indonesia (BANI). The methodology adopted for the study included case studies, interviews and industry wide questionnaire survey. The respondens for the study include the clients, contractors and the authority involved in regulating Indonesia Construction Industry in the province of West Sumatra, Jakarta and Batam. The study found that one of the main sources of the claim is due to the act of the clients themselves especially with regard to changes in the scope of work. On the other hand the contractor also have significance contribution toward such issues. Most of the disputes and claims problems are solved through negotiation channel. The study also found that the role and effectiveness of Badan Arbitrase Nasioanal Indonesia (BANI) in resolving the dispute problems is quite limited. Various proposals have been made in this study toward improving the process of resolving the constuction disputes and claims in Indonesia as well as the roles of Badan Arbitrase Nasioanal Indonesia (BANI)